2023
DOI: 10.3390/beverages9020030
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Non-Thermal Technologies for Wine Processing, Preservation, and Quality Enhancement

Abstract: Recently, non-thermal wine processing technologies have been proposed as alternatives to conventional winemaking processes, mostly with the aims to improve wine quality, safety, and shelf-life. Winemakers typically rely on sulfites (SO2) to prevent wine oxidation and microbial spoilage, as these processes can negatively affect wine quality and aging potential. However, SO2 can trigger allergic reactions, asthma, and headaches in sensitive consumers, so limitations on their use are needed. In red winemaking, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Regarding grape sanitation, HPP, microwave, and irradiation appear to be the most promising techniques (Kumar et al, 2023). The authors suggested that this reduction might be due to an increase in condensation reactions of phenolic compounds in wines promoted by HPP.…”
Section: Phenolic Compounds: From Grape To Winementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding grape sanitation, HPP, microwave, and irradiation appear to be the most promising techniques (Kumar et al, 2023). The authors suggested that this reduction might be due to an increase in condensation reactions of phenolic compounds in wines promoted by HPP.…”
Section: Phenolic Compounds: From Grape To Winementioning
confidence: 99%
“…Most of these techniques fall under the category of nonthermal wine processing technologies. A comprehensive review of these cutting‐edge winemaking strategies is available in the literature (Kumar et al., 2023). Some of them are already in use, such as high‐pressure processing (HPP), pulsed electric field (PEF), and ultrasound, while microwave and irradiation are employed at the laboratory scale.…”
Section: Phenolic Compounds: From Grape To Winementioning
confidence: 99%
See 1 more Smart Citation